Fam??lia, transtornos alimentares e obesidade na adolesc??ncia: estudo por meio do Rorschach e da abordagem sist??mica - Bergma, Ilckmans Tonh?? Moreira Mugarte (2012)
Eating disorders such as anorexia and bulimia nervosa, considered as serious disturbances in eating habits, are relevant causes of morbidity and mortality in adolescents. Patients with these disorders have a mortality rate twelve times higher than the normal population in the same age range. Obesity may be considered one of the world???s most serious public health problems, because of the complications associated with it and the high rates of morbidity and mortality. Eating disorders and obesity have been studied in past years, however most researches focuses on the individual aspects of the patients. It was with the intent to broaden the comprehension of these diagnosis, also involving the family context of individuals, that this present study aims at establishing possible links between the answers given by the adolescents with eating disorders (bulimia nervosa and anorexia nervosa) and obesity, in regards to the parental figures in the Rorschach method and the characteristics of the family dynamic, identified by means of systemic techniques. The project is part of a larger project which aims at building a psychosocial care methodology for children and adolescents with eating disorders and their families, which is in progress at Universidade Catolica de Brasilia, under the coordination of this dissertation???s advisor and of which the author is also part of. The participants were three families which resides in Administrative Regions of the Federal District: the first has an adolescent with a diagnosis of anorexia nervosa, composed by the mother, 46 years of age, and a sister who is 17, they live in a rental home and have a monthly income of $2.700,00; the second has an adolescent with a bulimia nervosa diagnosis, composed by the mother who is 42 years old, father, 43, and two brothers of 22 and 07, they live in a home which they own and have a monthly income of two minimum wages; the third which has a diagnosis of obesity is composed by the mother, 67 years old, two sisters of 26 and 21, and a brother of 23, they live in a home which they own and have an approximate monthly income of two minimum wages. Qualitative research method was used by means of case study. A semi-structured family interview ??? Family Life Cycle Interview was conducted, with the elaboration of a genogram and, afterwards, the adolescents were submitted to the Rorschach test. The data from the interviews were analysed based on the constructiveinterpretative method of Gonz??les Rey and the data from the tests were analysed according to the Rorschach protocols, based on the French School. The data found regarding the Family Life Cycle and history showed a few characteristics of the family dynamic such as: difficulties on the maternal side of the families; difficulties in the adolescents??? social relationships; a disengaged family structure (in the family with anorexia nervosa), family with diffused external borders (bulimia nervosa) and an enmeshed family structure (family with obesity); current irregular eating habits (families with anorexia and obesity) and abundance and variety in the current eating habits (family with bulimia); food as a gathering factor (families with bulimia and obesity). The data from the Rorschach test showed the presence of low self-esteem, insecurity, distortions of self-concept and self-image and sexual identification problems among the adolescents.